Number 51 (December 2009) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2009)
(December 2009) - Post-impoundment Changes in the Cyprinid Fauna of the Lower Sabine River, Louisiana and Texas By Royal D. Suttkus and Maurice F. Mettee The Desperate Dozen: Southeastern Freshwater Fishes on the Brink. By Bernard R. Kuhajda, Anna L. George, and James D. Williams Prioritizing Areas of the Conasauga River Sub-basin in Georgia and Tennessee for Preservation and Restoration. By Seth J. Wenger, Megan M. Hagler, and Byron J. Freeman. State Southeastern Fishes Council State Reports Minutes, Business Meeting, 34th Annual Meeting, Southeastern Fishes Council 2008 Treasurer's Report for the Southeastern Fishes Council
Keywords: cyprinid fauna; lower sabine; southeastern; fresh water; fishes; conasauga river